Genetic variation in CaTIFY4b contributes to drought adaptation in chickpea. Issue 9 (21st May 2022) - Barmukh, Rutwik; Roorkiwal, Manish; Garg, Vanika; Khan, Aamir W.; German, Liam; Jaganathan, Deepa; Chitikineni, Annapurna; Kholova, Jana; Kudapa, Himabindu; Sivasakthi, Kaliamoorthy; Samineni, Srinivasan; Kale, Sandip M.; et al.
Summary: Chickpea production is vulnerable to drought stress. Identifying the genetic components underlying drought adaptation is crucial for enhancing chickpea productivity. Here, we present the fine mapping and characterization of ' QTL‐hotspot ', a genomic region controlling chickpea growth with positive consequences on crop production under drought. We report that a non‐synonymous substitution in the transcription factor CaTIFY4b regulates seed weight and organ size in chickpea. Ectopic expression of CaTIFY4b in Medicago truncatula enhances root growth under water deficit. Our results suggest that allelic variation in ' QTL‐hotspot ' improves pre‐anthesis water use, transpiration efficiency, root architecture and canopy development, enabling high‐yield performance under terminal drought conditions. Gene expression analysis indicated that CaTIFY4b may regulate organ size under water deficit by modulating the expression of GRF‐INTERACTING FACTOR1 ( GIF1 ), a transcriptional co‐activator of Growth‐Regulating Factors. Taken together, our study offers new insights into the role of CaTIFY4b and on diverse physiological and molecular mechanisms underpinning chickpea growth and production under specific drought scenarios.